Szczegółowe kwestie polityki prawa - Municzewski, Andrzej; Majchrowski, Jan; Sut, Paweł (Wydział Prawa i Administracji UAM, 1994)
Certain detailed issues of the policy of law are considered. The authors emphasise the axiological aspect of the application of law as a social influence. A. Municzewski reconstructs the purposes and effects of amnesty acts in Poland, pointing to a short-lived result of amnesty in the whole process of penal policy-making. Certain other aspects of a number of amnesty acts in Poland have also been revealed. J. Majchrowski writes about social costs incurred when the law is utilised as an instrument helping to achieve certain emergency or temporary goals. This is illustrated on the example of the electoral act to local governments in Poland. P. Sut postulates a reform of the sphere of intimacy in the Polish law, by, on the one hand providing an explicit definition of the 'sphere of intimacy' and differentiation it from the 'sphere of privacy', and on the other hand by implementation of a more extensive responsibility to indemnify a person for damages when that sphere has been infringed.
Certain detailed issues of the policy of law